Promoting Blended Learning in Vocabulary Teaching through WhatsApp - Mokh Arif Bakhtiyar (Prodi Manajemen Pendidikan Islam Institut Pesantren KH Chalim Mojokerto, 2017)
Notwithstanding some non-English speaking countries' curriculum has changed over time, the students' vocabulary acquisition remains pathetic. The evidence of the plight of students' mastery on vocabulary can be easily and obviously found on their daily basis activity of English learning. Teachers are encouraged to employ various approaches, methods, or strategies to meet the goal of the improvement of pupils' vocabulary. This article suggests an idea of how to develop it through the use of WhatsApp. It has now been ubiquiotous application attached in students' smartphone which brings through students and teachers to be connected anytime and anywhere. The utilization of WhatsApp in language teaching is believed to prompt learners' motivation which in the end will lead them to learn vocabulary effectively.